Attic Oratory and Performance - Serapheim, Andreas (Routledge Monographs in Classical Studies, 2017)
Cover -- Half Title -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- Acknowledgments -- Abbreviations -- Introduction -- Current perspectives and approaches -- What this book is about -- Performance Studies and Attic oratory -- Audience and speaker in the law-court -- Four case studies -- The Embassy Case -- The Crown Case -- Outline -- 1 The hermeneutic framework -- The notion of performance: Conceptual groundwork -- Performance in the theatre and the law-court -- Judicial oratory in/as performance: Aeschines 2, 3 and Demosthenes 18, 19 -- Constructed audience -- Other strategies to influence the audience -- Reconsidering ekphrasis through the lens of ancient theory -- The depiction of litigants, ēthopoiia -- Conceptual groundwork -- The performative dimension of oratorical portraiture -- Inter-generic portraiture -- Hypocrisis - delivery -- Script, revision and extemporisation -- A note on the use of ancient sources -- 2 Construction and manipulation -- Addresses to the audience and civic community -- Law-court 'Big Brother'! -- Emotional appeals -- Direct/explicit appeals to emotions -- Indirect/inexplicit appeals to emotions -- Defence versus prosecution -- The language of performance: Imperatives and questions -- 3 Aeschines and Demosthenes in the theatre of justice -- Political thespians in the law-court -- The use of quotations -- 'He is proud of his voice': Oral excess in the law-court -- 'Drive him away and hiss him out': Inviting the audience reaction -- 4 Ēthopoiia: An inter-generic portrayal of character -- Comic or laughter-inducing ēthopoiia -- Comic stereotyping -- Inversion of tragedy into comedy -- Ridiculing sexuality -- Character portraiture: Tragedy and epic -- Identification with tragic and epic characters -- Cursed or unlucky? -- 5 Hypocrisis! Hypocrisis! Hypocrisis! -- Hypocrisis of emotions.